The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/08870446.2013.843682
|View full text |Cite
|
Sign up to set email alerts
|

Postsurgical physical activity and fatigue-related daily interference in women with non-metastatic breast cancer

Abstract: Purpose Women undergoing surgery for breast cancer experience side effects such as fatigue, reduced quality of life (QOL), and depression. Physical activity (PA) is associated with improved psychological adjustment during treatment and survivorship, yet little is known about how PA relates to fatigue, depression and QOL in the period following surgery for breast cancer. The purpose of the study was to examine the relationships between these constructs in women who recently underwent surgery for breast cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 80 publications
(111 reference statements)
3
13
0
Order By: Relevance
“…It was concluded that women who were more physically active in the months after surgery, psychologically adapted much better in the early stages of treatment, with fewer symptoms of fatigue and higher QOL. 21 Our study showed a significant positive correlation between QOL (EORTC-QLQ-30) and PA (p<0.001). It was observed that the most active women had better rates in all the scales, especially for functional capacity (p<0.001).…”
Section: Resultssupporting
confidence: 53%
“…It was concluded that women who were more physically active in the months after surgery, psychologically adapted much better in the early stages of treatment, with fewer symptoms of fatigue and higher QOL. 21 Our study showed a significant positive correlation between QOL (EORTC-QLQ-30) and PA (p<0.001). It was observed that the most active women had better rates in all the scales, especially for functional capacity (p<0.001).…”
Section: Resultssupporting
confidence: 53%
“…In a randomized-controlled trial a combination of self-directed stress management training and home-based exercise increased self-reported physical activity levels and reduced depression and anxiety among 286 cancer patients, mainly diagnosed with breast and lung cancer, at the start of chemotherapy [13] . A similar tendency was seen in a cross-sectional study among 240 women with breast cancer, where an association between higher self-reported physical activity levels and reduced depression was found 2-10 weeks post-surgery [12] . In a cross-sectional study among 180 colon cancer survivors objectively recorded moderate-to-vigorous intensity physical activity was associated with anxiety but not depression [28] .…”
Section: Discussionsupporting
confidence: 82%
“…There are indications that physical activity may influence distress positively in cancer patients both during and after oncological treatment [10,11] . For adult cancer patients at the start of treatment, higher self-reported physical activity levels have been associated with reduced anxiety and depression [12,13] . In cohorts and in a retrospective study, it has been suggested that being physically active before cancer diagnosis and during early treatment may result in less depression [14,15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…The process by which physical activity reduces these symptoms is less understood [8]. Previously, women with non-metastatic breast cancer reported greater physical activity and had less concurrent perceived daily interference due to fatigue, less clinician- and self-rated depressive symptoms, and better functional QoL following surgery [9]. Moreover, fatigue interference served an intermediary role; greater physical activity was related to less depressive symptoms and better functional QoL via reduced fatigue interference [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, women with non-metastatic breast cancer reported greater physical activity and had less concurrent perceived daily interference due to fatigue, less clinician- and self-rated depressive symptoms, and better functional QoL following surgery [9]. Moreover, fatigue interference served an intermediary role; greater physical activity was related to less depressive symptoms and better functional QoL via reduced fatigue interference [9]. While these findings suggest a potential mechanism relating physical activity to mood outcomes, the relationships must be examined longitudinally for better understanding.…”
Section: Introductionmentioning
confidence: 99%